Predictors of drug-related problems among psychiatric patients with anxiety disorders: a systematic review - Andi Ayulestari; Atika Wahyu Puspitasari; Nadia Farhanah Syafhan (Faculty of Pharmacy, Universitas Pancasila, 2026)
Anxiety disorders are a major component of mental health conditions and are commonly managed with long-term pharmacotherapy, including the use of antidepressants and anxiolytics. The complexity of these regimens increases the risk of drug-related problems (DRPs), which may compromise treatment effectiveness, patient safety, and adherence to medication. This systematic review aimed to identify and synthesize the risk factors associated with DRPs in patients with anxiety disorders. A comprehensive systematic search was conducted across electronic databases according to the PRISMA guidelines. Observational studies were included to reflect real-world clinical practice, and the methodological quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS). Studies published between 2016 and 2026 were considered; however, only eligible studies published between 2022 and 2025 were included in the final analysis. Ten studies involving 151,331 participants from inpatient and outpatient settings were analyzed. Polypharmacy was the most consistently reported predictor of DRPs (7/10 studies). Other commonly identified risk factors included comorbidities (7/10), older age (6/10), use of multiple psychotropic medications (6/10), longer treatment duration or hospitalization (5/10), poor medication adherence (5/10), and inappropriate dosing (4/10). Patients with anxiety disorders are at considerable risk of DRPs, with polypharmacy being the most critical predictor. These findings highlight the importance of targeted pharmaceutical care interventions, including medication reviews, deprescribing, and adherence optimization, as well as the key role of pharmacists in improving pharmacotherapy outcomes.